(untitled) (Costos y Gestión, 2021)
The aim of this project is to address the complete process of manufacturing a type of pneumatic bellows used in cargo trucks, from my own initial experience in this industry. This model was conceived of as a nationally manufactured alternative to competing imported products, but with an important differentiation: that it could be taken-apart into individual longer lasting components. In international markets, the unit is manufactured in a sealed form, that is to say, that when it is necessary to replace it, either because it has broken or because it has lost its power through use, the entire sealed unit is replaced, as a whole, by a new one. The intention of this alternative is to help reduce, to some extent, the cost of replacement. Usually, what happens first is the rupture of the rubber bellows, but not any of the other component parts, in which case, the dismantlable unit fulfills its function by continuing to use the parts that are in good condition, whilst changing those that are not. The vehicles that use this parts, for example, trucks and agricultural machinery, have found a viable alternative in these products, which maintains performance and reduces associated costs. The study of these processes aims to provide an accurate representation of the information acquired so that the business owner can determine clearly, and with the highest possible degree of accuracy, the costs involved in each of them, as well as to provide management tools on which they can rely during the decision-making process. I say that this is the beginning of a long road, because the objective is to cost out all the products that the business manufactures. Within this wide range, there is a certain complexity in the processes. There are products with sequential manufacturing processes, others with parallel sub-processes and sequential sub-processes. Given the multiple production alternatives, it will vary depending on how different factors are applied one way or another and how the processes are set up to achieve the final product.